2018
DOI: 10.1136/bmjopen-2017-020341
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features, bacteriology of endotracheal aspirates and treatment outcomes of patients with chronic obstructive pulmonary disease and community-acquired pneumonia in an intensive care unit in Taiwan with an emphasis on eosinophilia versus non-eosinophilia: a retrospective case–control study

Abstract: ObjectivesThe clinical implications of blood eosinophil level in patients with chronic obstructive pulmonary disease (COPD) and community-acquired pneumonia (CAP) requiring invasive mechanical ventilation (IMV) and intensive care unit (ICU) admission are still unknown. Thus, this study aimed to compare the features of such patients with and without blood eosinophilia.DesignThis was a retrospective case–control study.SettingAn ICU of a medical centre in central Taiwan.ParticipantsA total of 262 patients with CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 48 publications
0
12
2
Order By: Relevance
“…In this study, we found that the severity of airflow limitation defined based on GOLD grades was an independent factor associated with short-term in-RCC treatment outcomes in terms of mechanical ventilator weaning and presence of any adverse outcomes of interest 6 . Previously, we also found that blood eosinophil level was significantly associated with the in-ICU treatment outcome of ICU length of stay 22 . Taken together, this information provides evidence that these two biomarkers have predictive value and are helpful for physicians when managing patients with COPD and PMV and those critically ill with COPD.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In this study, we found that the severity of airflow limitation defined based on GOLD grades was an independent factor associated with short-term in-RCC treatment outcomes in terms of mechanical ventilator weaning and presence of any adverse outcomes of interest 6 . Previously, we also found that blood eosinophil level was significantly associated with the in-ICU treatment outcome of ICU length of stay 22 . Taken together, this information provides evidence that these two biomarkers have predictive value and are helpful for physicians when managing patients with COPD and PMV and those critically ill with COPD.…”
Section: Discussionmentioning
confidence: 64%
“…Peripheral blood eosinophil level may be an useful indicator of treatment outcomes when managing patients with COPD, as a number of studies have demonstrated associations between blood eosinophilia and a lower risk of pneumonia, a shorter length of hospital stay, and better quality of life and survival in patients with stable COPD. Furthermore, these studies have also demonstrated associations between blood eosinophilia and a shorter ICU length of stay in patients with COPD and community-acquired pneumonia that require admission to an ICU and support by invasive mechanical ventilation 1922 . However, we found that blood eosinophilia using 2%, 4%, 150 cells/μL, and 300 cells/μL as thresholds was not associated with any short-term in-RCC treatment outcomes in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The study setting and population have been described previously. 10 Briefly, this retrospective, cross-sectional study included spirometrically confirmed COPD patients complicated with CAP, who required IMV on arrival at the emergency department (ED) as per physician assessment of the patient’s clinical status and an admission to the RICU at Taichung Veterans General Hospital (TCVGH), which is located in central Taiwan from January 2005 to December 2015. Individuals with tracheostomy, receiving endotracheal intubation before arrival of the ED, or a history of bronchiectasis, asthma, lung cancer and other respiratory diseases were excluded from this study.…”
Section: Methodsmentioning
confidence: 99%
“…The diagnostic criteria for COPD and CAP have been previously reported in detail. 10 Shortly, COPD was diagnosed spirometrically for all patients according to Global Initiative for Chronic Obstructive Lung Disease (GOLD) 2017 recommendations. 14 The diagnosis of pneumonia was made based on radiological and clinical criteria while CAP was confirmed if patients were not documented as having healthcare-associated pneumonia, HAP or VAP in the medical records of the ED on admission, and if they had not been hospitalized in the month prior to the development of pneumonia or resided in long-term care facilities.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation